2023
DOI: 10.6026/97320630019336
|View full text |Cite
|
Sign up to set email alerts
|

Assigning new supergroups V and W to the Wolbachia diversity

Abstract: Wolbachia are endosymbiotic and alphaproteobacteria that belong to the order Rickettsiales. They are known to infect half of the insect population and cause host manipulation, and have been categorized into 19 monophyletic lineages called supergroups. Recently, two strains, wCfeJ and wCfeT were isolated from cat fleas (Ctenocephalides felis), but their supergroup relationships were not assigned. In this article, we have attempted to classify these two novel strains and establish their evolutionary lineage (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Wolbachia is a widespread intracellular bacterial symbiont that has been isolated from various insect species, ticks, and nematodes [20][21][22]. The Wolbachia genus has only one species, which has recently, based on gene sequence information, been classified into 21 major clades of Wolbachia known as 'supergroups' (A-F, H-Q, and S-W), with each group being classified into dozens of different subgroups, often based on analysis of the bacterial surface protein (wsp) [23][24][25][26][27][28][29]. Supergroups A and B are known to exclusively infect arthropods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wolbachia is a widespread intracellular bacterial symbiont that has been isolated from various insect species, ticks, and nematodes [20][21][22]. The Wolbachia genus has only one species, which has recently, based on gene sequence information, been classified into 21 major clades of Wolbachia known as 'supergroups' (A-F, H-Q, and S-W), with each group being classified into dozens of different subgroups, often based on analysis of the bacterial surface protein (wsp) [23][24][25][26][27][28][29]. Supergroups A and B are known to exclusively infect arthropods.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that different primer sets vary in their capability to detect Wolbachia in their hosts [35]. Different molecular markers such as 16s rRNA, ftsZ and wsp have been widely used to detect and to study the phylogenetics of Wolbachia [28,36], however, several investigations have shown the false negative for ftsZ [21,37,38] or false positive results for 16s rRNA and wsp markers in discriminating between supergroups A and B which can lead to unreliable results in bacterial detection when these primer sets are used alone [39]. Besides, detection of recombination both between and within Wolbachia genes [40] suggests that a single-locus approach to strain characterization may be misleading [41].…”
Section: Introductionmentioning
confidence: 99%